The Synaptic Ribbon Is a Site of Phosphatidic Acid Generation in Ribbon Synapses - Schwarz, Karin (J Neurosci, 2011)
Ribbon synapses continuously transmit graded membrane potential changes into changes of synaptic vesicle exocytosis and rely on intense synaptic membrane trafficking. The synaptic ribbon is considered central to this process. In the present study we asked whether tonically active ribbon synapses are associated with the generation of certain lipids, specifically the highly active signaling phospholipid phosphatidic acid (PA). Using PA-sensor proteins, we demonstrate that PA is enriched at mouse retinal ribbon synapses in close vicinity to the synaptic ribbon in situ. As shown by heterologous expression, RIBEYE, a main component of synaptic ribbons, is responsible for PA binding at synaptic ribbons. Furthermore, RIBEYE is directly involved in the synthesis of PA. Using various independent substrate binding and enzyme assays, we demonstrate that the B domain of RIBEYE possesses lysophosphatidic acid (LPA) acyltransferase (LPAAT) activity, which leads to the generation of PA from LPA. Since an LPAAT-deficient RIBEYE mutant does not recruit PA-binding proteins to artificial synaptic ribbons, whereas wild-type RIBEYE supports PA binding, we conclude that the LPAAT activity of the RIBEYE(B) domain is a physiologically relevant source of PA generation at the synaptic ribbon. We propose that PA generated at synaptic ribbons likely facilitates synaptic vesicle trafficking.